Odpowiedź :
Odpowiedź:
[tex]\huge\boxed{a=5;\ b=9;\ c=-15}[/tex]
Szczegółowe wyjaśnienie:
[tex](3x+ay)(bx^2+cxy+25y^2)=27x^3+125y^3[/tex]
Z doświadczenia widzę, że po prawej stronie jest zastosowanie wzoru skróconego mnożenia:
[tex]a^3+b^3=(a+b)(a^2-ab+b^2)[/tex]
czyli
[tex]27x^3+125y^3=(3x)^3+(5y)^3=(3x+5y)\bigg((3x)^2-3x\cdot5y+(5y)^2\bigg)\\\\=(3x+5y)(9x^2-15xy+25y^2)[/tex]
Stąd:
[tex](3x+5y)(9x^2-15xy+25y^2)=(3x+ay)(bx^2+cxy+25y^2)[/tex]
Z równości wnioskujemy, że:
[tex]5y=ay\to \boxed{a=5}\\\\9x^2=bx^2\to\boxed{b=9}\\\\-15xy=cxy\to\boxed{c=-15}[/tex]